Wearing Data: from McLuhan's "Extended Skin" to the Integration Between Wearable Technologies and a New Algorithmic Sensibility - Barile, Nello; Sugiyama, Satomi (Fashion theory, 2020)
One of the current issues in fashion studies resides in the area of wearable technologies research. The intersection between fashion and technology has been studied; however, as technology, particularly information and communication technologies (ICTs), evolves at a rapid speed, this topic has become increasingly important in recent years. This paper proposes to apply Marshall McLuhan's ideas on media and fashion as an analytical framework of wearable technologies, particularly focusing on the case of Hussein Chalayan. The analysis of Chalayan's work suggests the progressive integration between design innovation and increasingly elaborate storytelling techniques. The paper argues that the smartly clothed body produces data as well as wears the data. The extended skin is equipped with artificial sensory systems, extending our natural body and sensory systems into the augmented space; the extended skin is datafied and the body is datafied.